Memory dispensing machine 《藝-味販賣機》 - Chua, Felicia Qin Ying (Nanyang Technological University, 2021)
Memory Dispensing Machine explores the connection between experience and play. Using the vending machine as an avenue to create a marriage between consumer goods and education, bringing together people of all ages, pathing a way for strangers to connect over experiences.